Design of a Compact Circular Waveguide Antenna of Low Polarization Level using EBG Structures - Gómez, Josefa; Tayebi, Abdelhamid; González, Iván; Cátedra, Felipe (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A new technique to improve the performance, in terms of bandwidth, gain and polarization purity, of conventional circular waveguide antennas using an electromagnetic band gap (EBG) structure is presented. The proposed antenna is composed by a circular waveguide and two layers with squared holes located over the waveguide aperture. The dimensions of the antenna have been obtained by means of an optimization process that uses a rigorous analysis tool. According to the results, a notable enhancement in polarization purity and gain is demonstrated when incorporating the second grid. The EBG antenna has the peak gain 14.36 dBi and the cross polarization level is lower than 40 dB within a wide bandwidth of 17%. A prototype has been fabricated and measured operating at 9.1GHz.